Analyzing the Impact of Google Earth on the Learning Motivation of Elementary School Students - Fatayan, Arum (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aims to determine the effect of Google Earth on the learning motivation of elementary school students in Jakarta using the RADEC (Read, Answer, Discuss, Explain, and Create) model. The sample consists of 40 fifth-grade students from a Jakarta elementary school. This is qualitative and quantitative research. The study's average results indicate that using Google Earth motivates 45.5% of students to learn. Before and after using Google Earth, based on the presentation, there was an increase of 23% in the learning motivation of Jakarta elementary school students. Before using Google Earth, student learning motivation was at 34%. Meanwhile, after using Google Earth, students' learning motivation increased by 57%. This study uses the RADEC model (Read, Answer, Discuss, Explain, and Create) in teaching and learning activities. Then, we discovered that Google Earth had an influence on indicators of students' learning motivation, such as their desire to learn, their needs, their ability to reach goals, their encouragement, and the creation of a pleasant learning atmosphere. Earth. The RADEC model with Google Earth technology further increases elementary school students' learning motivation compared to the RADEC model without Google Earth technology.